Basic and clinical science course 1990-1991. Section 1, Fundamentals and principles of ophtalmology (American Academy of Ophthalmology, 1990)
The textbook provides a curriculum that focuses on basic and clinical science and on ophthalmology. Intended for professional public and for university students.
Keywords: věda a výzkum; klinické lékařství; kurikulum; Clinical Medicine; věda; Science; Ophthalmology; oftalmologie; Curriculum